Peran Kepemimpinan Kepala Kantor Urusan Agama dalam Meningkatkan Kedisiplinan Pegawai di Kecamatan Sumberjaya - Kurniawan, Eki; Sanusi, Irfan; Herman, Herman (Tadbir: Jurnal Manajemen Dakwah, 2022)
The purpose of writing this journal is to find out how the leadership role of the Head of the Sumberjaya Religious Affairs Office is. This study uses a descriptive method and a qualitative approach. From the results of research on the leadership role of the Head of the Office of Religious Affairs in improving employee discipline, it is known that the leadership style applied by the Head of the Office of Religious Affairs in Sumberjaya District is a bureaucratic, participatory, delegative and free-control leadership style. The leadership function is implemented optimally and the process of moving employees (actuating) is carried out by coordinating, providing motivation, creating good communication and providing guidance. The presence of the Head of the Office of Religious Affairs is able to improve the discipline of his employees.